2009
DOI: 10.1007/s11738-009-0384-2
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses to NaCl stress in three wild species of potato in vitro

Abstract: In this study, responses of wild species of potato to NaCl stress were investigated in vitro. In S. stoloniferum and S. bulbosum, length of the shoot, fresh and dry weight, photosynthetic pigments, K ? concentration, K ? /Na ? ratio, ascorbate pool, anthocyanin, and phenolic and flavonoid compounds were decreased in response to salinity. In these species, salinity increased the level of Na ? , lipid peroxidation, proline and ion leakage percentage. In S. acaule, the length of the shoot, and fresh and dry weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
64
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 52 publications
14
64
0
Order By: Relevance
“…However, high salinity induced a decrease in the anthocyanin level in the salt-sensitive species of potatoes, (Daneshmand et al 2010). Plant tissues with a higher content of anthocyanins usually have a higher resistance to drought.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…However, high salinity induced a decrease in the anthocyanin level in the salt-sensitive species of potatoes, (Daneshmand et al 2010). Plant tissues with a higher content of anthocyanins usually have a higher resistance to drought.…”
Section: Phenolic Compoundsmentioning
confidence: 99%
“…This leads to cells retaining water and a consequent tendency to retain their turgor pressure under water deficit. Osmotic adjustment reduces the sensitivity of processes dependent on turgor, such as growth and stomatal activity, when the water potential falls [19].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of intraspecific variability with respect to osmotic adjustment [6,16,17,19,[20][21][22] and coleoptile growth [23,24] has been demonstrated in different crops. This, along with the possibility of identifying QTLs that control drought tolerance in seedling [25], and coleoptile growth [26], renders the study of coleoptile growth of great interest in the improvement of drought tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of anthocyanins in response to stress has been reported to be genotype dependent. Daneshmand et al (2010) observed in wild po- tato species under salinity stress a decrease in anthocyanin content in salt sensitive species and no change in salt-tolerant ones. Ploenlap and Pattanagul (2015) observed anthocyanin overaccumulation under drought stress in a drought-tolerant rice and reduced anthocyanin content in a drought-sensitive variety.…”
Section: Discussionmentioning
confidence: 79%